Star-shaped Poly(hydroxybutyrate)s from bio-based polyol cores via zinc catalyzed ring-opening polymerization of β-Butyrolactone. (5th November 2021) - Omar, Rawan; Shaik, Muneer; Griggs, Chloe; Jensen, Jevin D.; Boyd, Robert; Oncel, Nuri; Webster, Dean C.; Du, Guodong
Graphical abstract: Highlights: Star-shaped poly(hydroxybutyrate)s are produced by ROP of β -butyrolactone via a core first approach. The core structures can be bioderived. The thermal properties and wettability can be correlated with the number of arms. Abstract: The ring-opening polymerization (ROP) of cyclic esters using multifunctional initiators is an efficient methodology that allows the preparation of polyesters with well-defined architectures. Here a series of star-shaped poly(β-hydroxybutyrates) (PHBs) has been synthesized by ROP of β -butyrolactone (BBL) with an amido-oxazolinate zinc catalyst. The star-shaped structure is constructed via a core-first approach, in which several bio-based multifunctional alcohols serve as the initiator for ROP. Specifically, three-, four-, and multi-armed star polymers are obtained and characterized by various techniques including NMR, GPC, TGA, and DSC, and the incorporation of the core structure in the star-shaped PHBs has been confirmed. The thermal properties can be modified by changing the arm number and arm length of PHBs, and the thermal stability decreases as the number of arms increases when they have the same arm lengths. The wetting behavior determined from AFM studies demonstrates a minimum in the macroscopic contact angle as a function of the number of arms of a star-shaped PHB.